9.8k views
1 vote
Use the fundamental identities to fully simplify the expression.

tanx sinx+ secx cos^2x. Explain how you do it

User Mtjhax
by
5.4k points

1 Answer

3 votes

Answer:

First, remember that:


tan(x) = (sin(x))/(cos(x))

and:


sec(x) = (1)/(cos(x))

Then we can rewrite the expression:


tan(x)*sin(x) + sec(x)*cos^2(x) = A

Where A is an equivalent expression.

as:


(sin(x))/(cos(x)) *sin(x) + (1)/(cos(x))*cos^2(x) = A

Then this is:


(sin^2(x))/(cos(x)) + cos(x) = A

Now we can multiply both sides by cos(x), then:


((sin^2(x))/(cos(x)) + cos(x))*cos(x) = A*cos(x)


sin^2(x) + cos^2(x) = A*cos(x)

And we know that the left term of the above equation is equal to 1, then:


1 = A*cos(x)


(1)/(cos(x)) = sec(x) = A

And A is equivalent to the original expression, then we get:


tan(x)*sin(x) + sec(x)*cos^2(x) = sec(x)

The simplification of the expression is sec(x)

User Homayoun
by
5.6k points